Anesthesia triggers drug delivery to experimental glioma in mice by hijacking caveolar transport. Issue 1 (20th September 2021) - Spieth, Lena; Berghoff, Stefan A; Stumpf, Sina K; Winchenbach, Jan; Michaelis, Thomas; Watanabe, Takashi; Gerndt, Nina; Düking, Tim; Hofer, Sabine; Ruhwedel, Torben; Shaib, Ali H; Willig, Katrin; et al.
Abstract: Background: Pharmaceutical intervention in the CNS is hampered by the shielding function of the blood–brain barrier (BBB). To induce clinical anesthesia, general anesthetics such as isoflurane readily penetrate the BBB. Here, we investigated whether isoflurane can be utilized for therapeutic drug delivery. Methods: Barrier function in primary endothelial cells was evaluated by transepithelial/transendothelial electrical resistance, and nanoscale STED and SRRF microscopy. In mice, BBB permeability was quantified by extravasation of several fluorescent tracers. Mouse models including the GL261 glioma model were evaluated by MRI, immunohistochemistry, electron microscopy, western blot, and expression analysis. Results: Isoflurane enhances BBB permeability in a time- and concentration-dependent manner. We demonstrate that, mechanistically, isoflurane disturbs the organization of membrane lipid nanodomains and triggers caveolar transport in brain endothelial cells. BBB tightness re-establishes directly after termination of anesthesia, providing a defined window for drug delivery. In a therapeutic glioblastoma trial in mice, simultaneous exposure to isoflurane and cytotoxic agent improves efficacy of chemotherapy. Conclusions: Combination therapy, involving isoflurane-mediated BBB permeation with drug administration has far-reaching therapeutic implications for CNS malignancies.